Elaboración de un bioinsecticida a partir del residuo agroindustrial del proceso de cocción del chocho (Lupinus mutabilis sweet), en la empresa la verde de la ciudad Machachi, cantón Mejía-Pichincha - Tandalla Pillo, Jessica Pamela (2022)
This research focuses on using the agro-industrial residue from the cooking process of lupine generated in the company "laVerde" in the elaboration of bioinsecticida. At the laboratory level, physicochemical and microbiological analyses were performed for the most relevant parameters, using the APHA method for alkalinity 236,27mg/L, conductivity 325,08s/cm, total solids 1652mg/L and turbidity 50,64NTU; under AOAC method for fat 0%, protein 3,07%, pH 5,47 INEN and carbohydrates under calculation 1,60%; through AOAC and ISO standard for total aerobes 1.2x106UFC/ml, molds 10upm/ml and yeasts 1. 3x106upl/ml. In addition, the alkaloids were quantified by (GC/MS), finding lupanine in the highest proportion with 54.52%, in relation to sparteine 18,17%, nuttalline 10,12% and isolupanine 0,56%. For the development of the bioinsecticide, the water was treated with centrifugation at 5000 rpm for 10 min and filtration in order to separate the organic matter, and pasteurized at 75°C for 15 min to eliminate the microorganisms present, establishing a composition of 88,5% lupine water and 11,5% auxiliary substances, with a pH of 5,07 at 54 days. Subsequently, the effectiveness on aphids and whiteflies was evaluated based on Abbott mortality, the dosage of 100ml and 75ml showed a mortality of 63% at 24h of exposure, reaching 85% and 75% of effectiveness at 72h for aphids, at the same dosages presented mortalities of 66% at 24h of exposure, reaching 75% and 83% of effectiveness at 72h for whiteflies.